2017
DOI: 10.1111/1758-2229.12579
|View full text |Cite
|
Sign up to set email alerts
|

Hydrography shapes community composition and diversity of amoA‐containing Thaumarchaeota in the coastal waters off central Chile

Abstract: Thaumarchaea are often abundant in low oxygen marine environments, and recent kinetic studies indicate a capacity for aerobic ammonia oxidation at vanishingly low oxygen levels (nM). However, molecular diversity surveys targeting this group to high sequencing coverage are limited, and how these populations are coupled to changes in dissolved oxygen remains unknown. In this study, the ammonia monooxygenase subunit A (amoA) gene was sequenced from samples collected in the Chilean coast (36.5 °S), a system prone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
(68 reference statements)
6
10
0
Order By: Relevance
“…The ammonia-oxidizing assemblages were predominantly characterized by N. maritimus-like followed by WCA amoA reaching higher abundances during winter, whereas the deep WCB amoA ecotype showing maxima during summer at the bottom. This result was supported by previous reports in the study area based on AOA amoA survey using clone libraries (Molina et al, 2010), and iTag sequencing (Bertagnolli and Ulloa, 2017) using primers designed by Pester et al (2012). These previous studies revealed specific predominant contribution of the WCA amoA in both upwelling and non-upwelling season and of the deep WCB amoA during the upwelling period.…”
Section: Contribution Of Ammonia Oxidizing Archaea Ecotypes In a Reprsupporting
confidence: 90%
See 1 more Smart Citation
“…The ammonia-oxidizing assemblages were predominantly characterized by N. maritimus-like followed by WCA amoA reaching higher abundances during winter, whereas the deep WCB amoA ecotype showing maxima during summer at the bottom. This result was supported by previous reports in the study area based on AOA amoA survey using clone libraries (Molina et al, 2010), and iTag sequencing (Bertagnolli and Ulloa, 2017) using primers designed by Pester et al (2012). These previous studies revealed specific predominant contribution of the WCA amoA in both upwelling and non-upwelling season and of the deep WCB amoA during the upwelling period.…”
Section: Contribution Of Ammonia Oxidizing Archaea Ecotypes In a Reprsupporting
confidence: 90%
“…Recently, ammonia and nitrite oxidation has been detected in this area at nanomolar concentrations of oxygen (5-33 nM, Bristow et al, 2016). Furthermore, molecular studies indicate the presence of an abundant and rich AOA community (Molina et al, 2010;Bertagnolli and Ulloa, 2017), as well as of Nitrospina spp., as the main drivers of nitrification under oxygen-deficient conditions at bottom waters during the spring-summer time (Levipan et al, 2014). In general, the water column is characterized by higher bacterioplankton abundances in summer (Galán et al, 2012), and Nitrosopumilus maritimus predominance (an important AOA ecotype at the Sta.18) in winter months based on metagenomic data (Murillo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our findings about regulation of N2O production at different stations probably apply to the region as a whole. Several studies indicate that water mass hydrography plays an important role in shaping microbial community diversity (Biller et al 2012, Hamdan et al 2012) and a coupling of amoA alpha diversity to physical conditions such as salinity, temperature and depth has 420 been shown in coastal waters off Chile (Bertagnolli and Ulloa 2017). While salinity, temperature and depth were prominent factors in shaping the community compositions of nitrifiers and denitrifiers ( Figure S4), for N2O production rates correlations with physical and chemical parameters were not consistent.…”
Section: Discussionmentioning
confidence: 93%
“…The structure of AOA populations follows different patterns in coastal waters. For instance, WCA organisms seem to be distributed at all depths, whereas WCB organisms are confined to low-O 2 and low-chlorophyll deeper waters in the Pacific coasts (Smith et al, 2014a;Bertagnolli and Ulloa, 2017). Additionally, AOA populations fluctuate seasonally, with abundance peaks during winter in the coastal Arctic and North Sea (Christman et al, 2011;Pitcher et al, 2011b), whereas in the Chilean coast, WCB organisms are abundant during spring and summer and non-detectable during winter (Bertagnolli and Ulloa, 2017).…”
Section: Distribution Of Nitrifier Communities In Marine Environmentsmentioning
confidence: 99%